Evaluation of a grid-independent solar photovoltaic system for primary health centres (PHCs) in developing countries. (March 2018) - Babatunde, Olubayo; Akinyele, Daniel; Akinbulire, Tolulope; Oluseyi, Peter
Highlights: A PV capacity of 3–6 kW is designed for a clinic's demand of 13–16.3 kWh/d. The PV system's yield and losses are 4.6 and 0.75 h/d. The PV system's life cycle cost is 14, 356– 14, 506 compared to 38, 135– 40, 460 for diesel system. The proposed PV system has the potential to avoid 8357–8956 kg/year of CO2 . Abstract : This paper presents the evaluation of a stand-alone solar photovoltaic (PV) electricity supply system for rural primary health centres (PHCs) in developing countries, using a PHC at Abadam local government area in North-West Nigeria as a case study. The paper is guided by standards for sizing and estimating the performance of stand-alone PV/battery systems. The research presents PV/battery/inverter capacity, yield and losses, battery state of charge, reliability and load growth analysis. The economic analysis is based on the life cycle cost assessment approach, while the environmental evaluation is considered in terms of the quantity of diesel fuel and carbon emissions avoided by the proposed solar PV system. A PV system capacity of 3.6–6 kW is designed for the clinic's total daily demand plus 25% load growth, with a yield of 4.6 h/d. This energy system can achieve a high availability over the year. The initial, life cycle, O and M and the replacement costs range from 14, 356 to 14, 506, 17, 909 to 18, 080, 1534 and 4451 to 4498, while the cost of energy ranges from 0.239 to 0.295/kWh. The diesel system which has an initial cost of 451 has a relatively higher life cycle cost of 38, 135– 40, 460. The proposed PV system has the potential to avoid 8357–8956 kg/year of CO2 after implementation.